Estimating rural-urban disparities in self-rated health in China: Impact of choice of urban definition - Audrey Dorélien; Hongwei Xu (Demographic Research, 2020)
Objective: We use the 2014 China Family Panel Studies (CFPS), which includes anchoring vignettes, to provide an up-to-date assessment of rural-urban health disparities as measured by self-rated health (SRH) in China. Our analysis is based on multiple definitions (hukou and the two different residence-based definitions) of rural-urban and migration status; previous research was inconclusive due to the use of different definitions and concerns about status-based differential health expectations (reporting heterogeneity). Results: We find a nonlinear difference between rural and urban Chinese in how they self-assess health status, regardless of the urban definition used. Urban respondents do not always hold a higher standard for self-assessment of health. Instead, their rating styles depend on the level of latent health. After controlling for the reporting heterogeneity, we find on average a slight urban advantage in SRH, but it is most pronounced when using the statistical (density dependent) definition of urban. Contribution: We study rural-urban health disparities based on three different urban definitions and migration status. Although we examine the urban definitions that are specific to China, we demonstrate a mindful approach when multiple definitions exist and caution against any simplistic approach that ignores context-specific urban definition. We also provide clear illustrations of the different types of reporting heterogeneity, as well as a way to visualize the cut-points, thresholds, and latent health estimates.